Arabidopsis WRKY2 and WRKY34 transcription factors interact with VQ20 protein to modulate pollen development and function. (20th July 2017) - Lei, Rihua; Li, Xiaoli; Ma, Zhenbing; Lv, Yan; Hu, Yanru; Yu, Diqiu
Summary: Plant male gametogenesis is tightly regulated, and involves complex and precise regulations of transcriptional reprogramming. WRKY transcription factors have been demonstrated to play critical roles in plant development and stress responses. Several members of this family physically interact with VQ motif‐containing proteins (VQ proteins) to mediate a plethora of programs in Arabidopsis; however, the involvement of WRKY–VQ complexes in plant male gametogenesis remains largely unknown. In this study, we found that WRKY2 and WKRY34 interact with VQ20 both in vitro and in vivo . Further experiments displayed that the conserved VQ motif of VQ20 is responsible for their physical interactions. The VQ20 protein localizes in the nucleus and specifically expresses in pollens. Phenotypic analysis showed that WRKY2, WRKY34 and VQ20 are crucial for pollen development and function. Mutations of WRKY2, WRKY34 and VQ20 simultaneously resulted in male sterility, with defects in pollen development, germination and tube growth. Further investigation revealed that VQ20 affects the transcriptional functions of its interacting WRKY partners. Complementation evidence supported that the VQ motif of VQ20 is essential for pollen development, as a mutant form of VQ20 in which LVQK residues in the VQ motif were replaced by EDLE did not rescue the phenotype of the w2‐1 w34‐1 vq20‐1 triple‐mutant plants. Further expression analysis indicated that WRKY2, WRKY34 and VQ20 co‐modulate multiple genes involved in pollen development, germination and tube growth. Taken together, our study provides evidence that VQ20 acts as a key partner of WRKY2 and WKRY34 in plant male gametogenesis. Significance Statement: Plant male gametogenesis is essential for plant propagation and strictly regulated, involving complex and precise regulations of transcriptional reprogramming. We report here that WRKY34 and WRKY2 transcription factors physically interact with VQ20 protein to form complexes, and their interactions affect the transcriptional function of those WRKY factors and mediate pollen development in Arabidopsis .